UI/UX Design with User Center Desgn Method For MUA Garut Wedding Booking Based On Mobile (Case Study : Ratna Beauty Makeup) - Nugraha, Yopi (RISTEC : Research in Information Systems and Technology, 2021)
At the stage booking a wedding in Ga rut district, especia lly for Ratna beauty makeup , which is still done manually or directly.stage booking and also information services are still carried out using socia l media such as Instagram, Facebook, Whatssap, and directly face to face with the customer have to go to ga llery repeated ly, sta rting from asking about wedding packa ges, information and also payment transactions. Even the admin is still doing it manually. Regarding the existence of these problems, resea rch is carried out by making user interface and user experience using the user centered design (UCD) . In this design, it is provided starting from the information page, packa ge selection, payment transactions with a variety of method options, and access design views for admins to check data and transactions on Ratna Beauty mak e-up.